Effect of Ethanol Extract of Wijaya Kusuma Leaves (Epiphyllum oxypetalum) as An Inhibitor of Salmonella typhi Bacteria - Ahada, M Tegar Suhitar; Nazip, Khoiron; Anggraini, Nike (Al-Kauniyah: Jurnal Biologi, 2025)
This study aims to determine the effect of ethanol extract of wijaya kusuma leaves (Epiphyllum oxypetalum) as an inhibitor and determine the Minimum Inhibitory Concentration (MIC) against Salmonella typhi bacteria. Quantitative research method with an experimental research design using a Completely Randomized Design (CRD) and the results were analyzed using One Way ANOVA test and continued with the Tukey test. Test method with disc diffusion method (Kirby-Bauer) in antibacterial test with extract concentration 0; 0.1; 0.2; 0.3; 0.4; 0.5; and 0.6% (g/v) and liquid dilution method in Minimum Inhibitory Concentration (MIC) test with extract concentration 0; 0.02; 0.04; 0.06; 0.08; and 0.1% (g/v). The results showed that ethanol extract of wijaya kusuma leaves (Epiphyllum oxypetalum) had a significant effect on Salmonella typhi bacteria with the best concentration of 0.6% which had a mean inhibition zone area of 45.05 ± 4.80 mm2 and the Minimum Inhibitory Concentration (MIC) was in the concentration range of 0 to 0.02% (g/v). The ethanol extract of wijaya kusuma leaves (Epiphyllum oxypetalum) has an effect as a growth inhibitor of Salmonella typhi bacteria.